Beowulf - Gummere, Francis Barton, 1855-1919.; Project Gutenberg (Salt Lake City : Project Gutenberg Literary Archive Foundation, 2006)
Beowulf first rescues the royal house of Denmark from two marauding monsters, then returns to rule his people for 50 years, ultimately losing his life in a battle to defend the Geats from a dragon's rampage.
Human-read audiobook.
Mode of access: World Wide Web.
Keywords: Scandinavia -- Fiction; Monsters -- Fiction; Dragons -- Fiction; Epic poetry, English (Old) -- Adaptations; Audiobooks